Inhibitive Bacterial MTT Assay for River Monitoring of Heavy Metals (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2013)
An inhibitive assay for metals using a MTT-bacterium assay system is presented. The assay is based on the ability of respiring bacteria to reduce the tetrazolium dye MTT. Out of the 13 metals screened, silver, mercury and copper exhibit strong inhibition to bacterial respiratory activity. The calculated IC50s for silver, mercury and copper were 0.068, 0.092 and 0.517 mg/L, respectively. The IC50 values obtained for these heavy metals are comparable and in certain cases lower than existing bioassay methods such as Daphnia magna, rainbow trout, Microtoxâ„¢ and papain assays. Works on real water samples from several rivers in Malaysia using the MTTâ€“bacterium assay showed positive correlation with instrumental method (ICP-OES) in detecting heavy metals. The bacterium was tentatively identified as S. marcescens strain Dr.YS8 based on carbon utilization profiles using Biolog GN plates and partial 16s rDNA molecular phylogeny. The system could be used to biomonitor heavy metals extensively in Malaysian waters.
Keywords: inhibitive assay; heavy metals; S. marcescens; MTT assay; Inhibitive assay; Heavy metals; S. marcescens; MTT assay